Healthcare providers' perspectives on perceived barriers and facilitators of compassion: Results from a grounded theory study. Issue 9 (May 2018) - Singh, Pavneet; Raffin‐Bouchal, Shelley; McClement, Susan; Hack, Thomas F; Stajduhar, Kelli; Hagen, Neil A; Sinnarajah, Aynharan; Chochinov, Harvey M; Sinclair, Shane
Abstract : Aims and objectives: To explore healthcare provider perspectives and experiences of perceived barriers and facilitators of compassion. Background: Compassion is considered a component of quality health care that healthcare providers are increasingly expected to provide. While there have been some studies exploring facets of healthcare providers' perspectives on the barriers and facilitators to providing compassion, a comprehensive understanding based on direct reports from healthcare providers is lacking. Design: Data were collected via focus groups and semi‐structured interviews. Data was analyzed in accordance with Straussian grounded theory. Methods: Semistructured focus groups with frontline healthcare providers and individual interviews with peer‐nominated exemplary compassionate care providers were audio‐recorded, professionally transcribed and analysed. Fifty‐seven participants were recruited from three healthcare settings within both rural and urban settings in Alberta, Canada, using convenience, snowball and theoretical sampling. Results: Qualitative analysis of the data generated two categories and associated themes and subthemes delineating perceived barriers and facilitators to compassion. The first category, challenges to compassion, reflects participants' discomfort associating the notion of barriers to compassion and contained several themes participants conceptualised as challenges: personal challenges, relational challenges, systemic challenges and maladaptive responses. The second category, facilitators of compassion, included the themes of personal facilitators, relational facilitators, systemic facilitators and adaptive responses of intentional action. Conclusion: Although participants described certain factors such as system and time constraints along with interaction styles of patients and families that can challenge healthcare provider compassion, these challenges were not considered insurmountable. While acknowledging these as challenges, participants identified healthcare providers themselves, including their responses towards the identified challenges of compassion, as significant factors in this process—a novel finding from this study. This study provides insight into healthcare providers' perspectives on the notion of barriers and facilitators in the provision of compassion. Relevance to clinical practice: This study provides a blueprint for optimising compassion on a personal, relational and system level.